TSV-based PUF circuit for 3DIC sensor nodes in IoT applications - Chao Wang; Jun Zhou; Guruprasad, Katti; Xin Liu; Weerasekera, Roshan; Kim, Tony T. (2015 IEEE International Conference on Electron Devices and Solid-State Circuits (EDSSC), 2015)
Sensor nodes massively deployed in Internet of Things are subject to physical capture, hardware tampering, device cloning, and unauthorized device alteration. This paper presented a novel ring oscillator PUF (Physical Unclonable Function) circuit exploiting the process variation of both CMOS devices and TSVs (Through Silicon Vias) available on TSV-based 3D stacking sensor nodes, for secure data generation resistant to physical attacks. As far as we know from the literature, this is the first work on TSV-based 3D PUF circuits. Simulation results based on a 0.18-μm CMOS technology and a 5.2-μm via-last TSV technology show that the proposed 3D PUF circuit has stronger uniqueness and reproducibility in PUF behavior.